Interpersonal violence and alcohol in the Russian Federation : policy briefing (WHO Regional Office for Europe, 2006)
Violent crime and alcohol consumption have increased considerably in the Russian Federation since the late 1980s with harmful health and social consequences for individuals, their families and friends and communities. Heavy alcohol consumption is closely associated with violent behaviour within the Russian Federation and internationally. The relationship between alcohol consumption and violent behaviour is complex, involving physiological, psychological, situational, social and cultural factors. Measures to control alcohol production and reduce consumption have reduced violent behaviour in the Russian Federation and elsewhere. However, round-the-clock sales, easy access to alcohol for minors and fierce economic competition between alcohol companies resulting in aggressive marketing techniques still need to be addressed in the Russian Federation. The multifaceted nature of alcohol-related violence highlights the need for a public health partnership involving health, social, education and criminal justice agencies. The Russian Federation is working closely with WHO to develop a public health approach to preventing violence
Keywords: Russia; Interpersonal Relations; Risk Factors; Spouse Abuse; Adolescent; směrnice jako téma; Child Abuse; domácí násilí; sociologie; Europe; zdravotní politika; interpersonální vztahy; Wounds and Injuries; násilí; Aged; senioři; Violence; mladiství; sexuologie; adiktologie; Evropa; Domestic Violence; veřejné zdravotnictví; rizikové faktory; Rusko; Sex Offenses; sexuální delikty; pití alkoholu; Alcohol Drinking; manželský partner - zneužití; rány a poranění; zneužívané dítě; Health Policy; Guidelines as Topic